All-polymeric multilayer para/ferroelectric dielectric films utilizing a gradient structure toward concurrent high discharge efficiency and energy density. (October 2022) - Li, Xinshuai; Shi, Zhicheng; Han, Mingli; Tang, Qingyang; Xie, Peitao; Fan, Runhua
Abstract: Polymeric dielectrics exhibit huge prospects for power electronic devices due to their ultrafast charge-discharge speed. However, a persisting challenge is that enhanced energy density always brings about deteriorated efficiency. Herein, a novel design of all-organic dielectric films, consisting of gradient transition layers sandwiched between a paraelectric layer and a ferroelectric layer, are prepared. It is interesting to find that the breakdown behaviors of the multilayer films are strongly dependent on the configuration of gradient transition layers. Consequently, via adjusting the configuration of gradient transition layers, a high breakdown strength of 623 kV/mm, an excellent efficiency of 89.5%, along with a high-energy density of 7.34 J/cm 3 are achieved. This work offers a unique route to develop polymeric dielectrics with concurrent high breakdown strength, high-energy density, and high efficiency. Graphical abstract: Image 1 Highlights: All-polymeric multilayer para/ferroelectric dielectric films utilizing a gradient structure is designed. The gradient structure optimizes electric field distribution and improves breakdown performance. Concurrent high-energy density and high efficiency are achieved by adjusting the configuration of gradient structure.